A comparative evaluation of osteoprogeterin and receptor activator of nuclear Kappa B ligand during orthodontic movement: Evaluasi komparatif osteoprogeterin dan aktivator reseptor ligan Kappa B nuklir selama gerakan ortodontik - Norman Hidajah; Ketut Virtika Ayu (Makassar Dental Journal PDGI Makassar, 2023)
Orthodontic tooth movement is a continuous and balanced process characterized by bone deposition and bone resorption res-pectively on tension and compression sites. This article is aimed to show the comparative of osteoprogeterin (OPG) and receptor activator of nuclear kappa B ligand (RANKL) during orthodontic tooth movement. Literature review was conducted by collect-ing various information regarding the topic and perform the synthesis. Several studies have shown the ratio concentration of RANKL to that OPG in gingival crevicular fluid was significantly higher than control sites. It was concluded that the OPG and RANKL expression during orthodontic movement varies at different time intervals and according to the type of force delivery system.